2018
DOI: 10.1021/acs.jpcc.7b11057
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Behaviors of M1Au24(SR)18 Nanoclusters: The Number of Valence Electrons Matters

Abstract: Doping is a quite useful strategy for probing the structure and properties of metal nanoclusters, but the effect of doping on the photodynamical properties is still not fully understood. Here, we reveal that the number of valence electrons plays a major role in determining the photodynamics of M 1 Au 24 (SR) 18 nanoclusters. By carrying out temperature-dependent optical absorption, it is found that Cd doping enhances electron−phonon coupling while Hg doping does not significantly alter the coupling. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(99 citation statements)
references
References 54 publications
7
86
0
Order By: Relevance
“…Modification of the metal composition has been studied for several clusters, but most research has focused on Au25(SR)18, which is an atomically precise cluster that has been long considered a convenient benchmark system for understanding properties and devising applications of gold nanoclusters. 10,11 Controlled doping of Au25(SR)18 − has been carried out with the noble metals platinum [12][13][14][15][16] and palladium, 14,[16][17][18][19] and less noble metals, such as cadmium [20][21][22] and mercury, 15,[20][21][22][23] also because of the ease by which monodoping could be achieved with these metals as opposed to, say, copper and silver. 9 Mass spectrometry and single crystal X-ray crystallography were extensively employed to interpret the doping results and, particularly, assign the specific locations where these single foreign-metal atoms go.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of the metal composition has been studied for several clusters, but most research has focused on Au25(SR)18, which is an atomically precise cluster that has been long considered a convenient benchmark system for understanding properties and devising applications of gold nanoclusters. 10,11 Controlled doping of Au25(SR)18 − has been carried out with the noble metals platinum [12][13][14][15][16] and palladium, 14,[16][17][18][19] and less noble metals, such as cadmium [20][21][22] and mercury, 15,[20][21][22][23] also because of the ease by which monodoping could be achieved with these metals as opposed to, say, copper and silver. 9 Mass spectrometry and single crystal X-ray crystallography were extensively employed to interpret the doping results and, particularly, assign the specific locations where these single foreign-metal atoms go.…”
Section: Introductionmentioning
confidence: 99%
“…In these demonstrations, one of the most important roles of the NCs is acting as a photosensitizer to extend the photoresponse of the semiconductor (i.e., TiO 2 ) from the UV to the Vis‐IR region . Advanced techniques such as time‐resolved optical spectrometry have been used to study the excited states of NCs . Several NCs (i.e., Au 25 and Ag 44 ) are reported to possess long‐lived excited states, which could favor the electron injection from the excited state of NCs to the conduction band of the semiconductor .…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] Advanced techniquess uch as time-resolved opticals pectrometry have been used to studyt he excited states of NCs. [29][30][31][32][33][34][35][36][37][38][39] Several NCs (i.e., Au 25 and Ag 44 )a re reportedt op ossess long-livede xcited states, which could favor the electroni njection from the excited state of NCs to the conduction band of the semiconductor. [29][30][31] However,i ti ss till unclear whether there are other important factors that affect the overall efficiency of the system.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm this, we extracted the ion intensities of Au 25¹x Ag x (SC 4 H 9 ) 18 (x = 04) from the time-dependent mass spectrum (Figure 14(a)). As shown in Figure 14 (Figure 16(a)) 148,286,507,568,603,706,721,767,768,791,795,813,826 and co-reduction method (Figure 16(b)). 43,58,174,219,222,241,262,300,305,311,346,356,431,536,587,601,614 In this study, we found that the isomer distribution also depends on the standing time in solution.…”
Section: Dependence Of Isomer Distribution On Preparative Conditionsmentioning
confidence: 94%